2003
DOI: 10.1001/archderm.139.9.1173
|View full text |Cite
|
Sign up to set email alerts
|

Pain Associated With Photodynamic Therapy Using 5-Aminolevulinic Acid or 5-Aminolevulinic Acid Methylester on Tape-Stripped Normal Skin

Abstract: Background: Pain during and after topical photodynamic therapy (PDT) is one of the few severe adverse effects of the new treatment of skin diseases.Objective: To compare the pain experienced in normal skin treated with 5-aminolevulinic acid (ALA) PDT and 5-aminolevulinic methylester (ALA-ME) PDT.Design: Double-blind randomized trial.Interventions: Twenty healthy volunteers were treated randomly with ALA-PDT on one forearm and ALA-ME-PDT on the other forearm after tape stripping of the sunexposed skin areas.Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 15 publications
4
109
2
3
Order By: Relevance
“…In one clinical trial, a small but significant association ( P  = 0.02, r 2  = 0.17) was found between the first sensation of pain and a delay greater than 30 min in exposure to daylight after the application of MAL cream 16. Together with anecdotal evidence from a retrospective case series,20 these findings suggest that patients who remain indoors for longer than 30 min after applying MAL cream may be at risk of increased pain, presumably arising from the greater accumulation of PpIX before sun exposure 23…”
Section: How To Treat Patients With Daylight Pdt With Methyl Aminolevmentioning
confidence: 94%
“…In one clinical trial, a small but significant association ( P  = 0.02, r 2  = 0.17) was found between the first sensation of pain and a delay greater than 30 min in exposure to daylight after the application of MAL cream 16. Together with anecdotal evidence from a retrospective case series,20 these findings suggest that patients who remain indoors for longer than 30 min after applying MAL cream may be at risk of increased pain, presumably arising from the greater accumulation of PpIX before sun exposure 23…”
Section: How To Treat Patients With Daylight Pdt With Methyl Aminolevmentioning
confidence: 94%
“…Irradiation-induced pain is thought to be associated with an effective PDT treatment taking place. Previous studies however have shown that pain scores do not correlate with the intensity of PpIX fluorescence either during ALA-PDT of tape stripped normal skin 20 or during ALA-PDT of skin cancer 22 . This suggests that pain associated with ALA-PDT is not simply due to the These findings are in contrast to studies using other iron chelating agents particularly DFO, where the addition of DFO to the higher ALA dose being employed in clinical treatment did not significantly enhance PpIX levels, when examined in matched lesions in the same patient 21 .…”
Section: Discussionmentioning
confidence: 87%
“…In a previous study it could be shown that MAL-PDT induces less pain in comparison to ALA-PDT which can be partially explained due to the differences in selectivity between the two substances [44].…”
Section: Practical Application Tolerability and Side Effectsmentioning
confidence: 98%